Evaluating the relationship between income, survival and loss of autonomy among older Canadians - Marie Connolly; Akakpo Domefa Konou; Marie-Louise Leroux (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2023)
Evaluating the relationship between health at old age and income is crucial for the design of equitable public policies targeted toward the elderly. Using 2016 Canadian survey data on adults aged between 50 and 70, we estimate the relationships between individual income, longevity and dependency at the old age. We use both subjective and objective measures of the probability to survive to age 85, of the probability to have activities of daily living (ADL) limitations, and of the probability of entering a nursing home. We find that income and the (objective and subjective) probability to live to age 85 and over are positively related while income and the (objective and subjective) probability to suffer from ADL limitations are negatively related. We also find that while the objective probability to enter a nursing home is negatively correlated with income, the subjective probability is positively correlated with income. Most of our results are driven by individuals in the highest tercile of the income distribution. Our results are robust to different sensitivity checks.
Keywords: C36; I10; I14; I18; J14; 330; Long term care; Survival probability; Probability to become dependent; Nursing home; Income